Therapeutic role of ursolic acid on ameliorating hepatic steatosis and improving metabolic disorders in high-fat diet-induced non-alcoholic fatty liver disease rats. - Songtao Li; Xilu Liao; Fanyu Meng; Yemei Wang; Zongxiang Sun; Fuchuan Guo; Xiaoxia Li; Man Meng; Ying Li; Changhao Sun (PLoS ONE, 2014)
Background Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent liver diseases around the world, and is closely associated with obesity, diabetes, and insulin resistance. Ursolic acid (UA), an ubiquitous triterpenoid with multifold biological roles, is distributed in various plants. This study was conducted to investigate the therapeutic effect and potential mechanisms of UA against hepatic steatosis in a high-fat diet (HFD)-induced obese non-alcoholic fatty liver disease (NAFLD) rat model. Methodology/principal findings Obese NAFLD model was established in Sprague-Dawley rats by 8-week HFD feeding. Therapeutic role of UA was evaluated using 0.125%, 0.25%, 0.5% UA-supplemented diet for another 6 weeks. The results from both morphologic and histological detections indicated that UA significantly reversed HFD-induced hepatic steatosis and liver injury. Besides, hepatic peroxisome proliferator-activated receptor (PPAR)-α was markedly up-regulated at both mRNA and protein levels by UA. Knocking down PPAR-α significantly inhibited the anti-steatosis role of UA in vitro. HFD-induced adverse changes in the key genes, which participated in hepatic lipid metabolism, were also alleviated by UA treatment. Furthermore, UA significantly ameliorated HFD-induced metabolic disorders, including insulin resistance, inflammation and oxidative stress. Conclusions/significance These results demonstrated that UA effectively ameliorated HFD-induced hepatic steatosis through a PPAR-α involved pathway, via improving key enzymes in the controlling of lipids metabolism. The metabolic disorders were accordingly improved with the decrease of hepatic steatosis. Thereby, UA could be a promising candidate for the treatment of NAFLD.